Impact of Green Accounting, Environmental Performance and Firm Size on Mining Financial Performance (2022–2024) - Chandra Selamat Putra Gulo; Erlina Erlina; Endang Sulistya Rini (Harmoni Economics: International Journal of Economics and Accounting, 2026)
This study aims to examine and analyze the influence of green accounting, environmental performance, and company size on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Financial performance is proxied by Return on Assets (ROA), green accounting is measured by the environmental cost ratio, environmental performance uses the PROPER rating, and company size is measured by the logarithm of total assets. This study uses secondary data obtained from annual reports, subscription reports, and other official publications. The analytical method used is panel data regression. The results show that green accounting has no effect on the financial performance of mining companies. This indicates that environmental costs incurred by companies have not been able to provide direct economic benefits in the short term. In addition, environmental performance has a negative effect on financial performance, indicating that increased environmental performance is also followed by a decrease in company profitability due to high compliance costs and environmental investments. Furthermore, company size has a negative effect on financial performance, indicating that the larger the company size, the greater the potential for operational inefficiencies and cost burdens that suppress the company's ability to generate profits. These findings suggest that corporate aspirations and scale growth efforts do not necessarily translate into improved financial performance in the short term.